Causes of Poverty in Old Age, Not a Structural Failing?. Issue 5 (20th October 2019) - Kola, Lola; Owumi, Bernard
ABSTRACT: The failures of many nations in Africa to include programs on aging into their national and developmental agendas have put more elderly people in the region at risk of poverty. Adult children are in many cases hampered from providing financial support to elderly parents due to waves of economic difficulties in many of the countries. The views of 36 elderly Nigerians were sought on causes of poverty in old age through key informant interviews. Despite awareness of structural causes, the results point to the direction of belief that individuals also have significant roles in determining their own economic fate in old age.